PENGARUH KAPITAL, UPAH KARYAWAN DAN BAHAN BAKU TERHADAP TINGKAT PENDAPATAN USAHA TAUKI DI PADANG BRAHRANG (Studi Kasus di UD Tauki Padang Brahrang) - Nur Aliah; Budi Abdullah; Gadis Arniyati Athar (Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine the influence of capital, labor and raw materials on the level of income of the Tauki business in Padang Brahrang and to determine the factors that most influence the increase in income of the Tauki business. The results of this research are the results of the t test for the capital variable (X1) obtained tcount of 0.328 with a probability of 0.746. The probability value is smaller than 0.05. Using a significance (α) of 0.05, the ttable value is 2.055. Thus tcount (0.328) < ttable (2.055). Shows that there is no positive and significant influence between capital (X1) on the income level of the tauki business at UD Tauki Padang Brahrang, Binjai City. The results of the t test for the employee wage variable (X2) obtained a tcount of 2.128 with a probability of 0.043. The probability value is smaller than 0.05 by using a significance (α) of 0.05, then the tcount value is 2.055. Thus tcount (2.128) > ttable (2.005). Shows that there is a positive and significant influence between employee wages (X2) on the income level of the tauki business at UD Tauki Padang Brahrang, Binjai City. The results of the t test for the raw material variable (X3) obtained a t count of 2.944 with a probability of 0.007. The probability value is smaller than 0.05. Using a significance (α) of 0.05, the ttable value is 2.055. Thus tcount (2.944) > ttable (2.055). Shows that there is a positive and significant influence between raw materials (X3) on the income level of the tauki business at UD Tauki Padang Brahrang, Binjai City. The results of the coefficient of determination test (r2) obtained a coefficient value of 0.772, meaning that 77.2% of the factors influencing the income level of the tauki business at UD Tauki Padang Brahrang can be explained by capital factors, employee wages and raw materials. Meanwhile, 22.8% (100%-77.2%) was explained by other factors not examined by researchers.